Association between HLA‐DQA1/DRB1 polymorphism and development of hepatocellular carcinoma during entecavir treatment. Issue 5 (26th September 2018) - Kozuka, Ritsuzo; Enomoto, Masaru; Sato‐Matsubara, Misako; Yoshida, Kanako; Motoyama, Hiroyuki; Hagihara, Atsushi; Fujii, Hideki; Uchida‐Kobayashi, Sawako; Morikawa, Hiroyasu; Tamori, Akihiro; Kawada, Norifumi; Murakami, Yoshiki
Abstract: Background and Aims: It remains unclear whether there is an association between single‐nucleotide polymorphisms (SNPs) and development of hepatocellular carcinoma (HCC) during entecavir (ETV) treatment in nucleos(t)ide analog‐naïve patients with chronic hepatitis B virus infection. We investigated the risk factors for HCC, especially host factors, during ETV treatment. Methods: A total of 127 Japanese patients undergoing ETV treatment were enrolled in this study. Univariate and multivariate analyses for clinical factors, hepatic fibrosis markers, and SNPs associated with HCC development were analyzed. Results: A total of 10 patients developed HCC during the follow‐up period (median duration, 3.3 years). The 3‐, 5‐, and 7‐year cumulative rates of HCC development were 4.8%, 10.6%, and 13.6%, respectively. Liver fibrosis (cirrhosis; P = 0.0005), age (≥ 49 years; P = 0.0048), platelet count (≤ 115 × 10/mm 3 ; P = 0.0007), α‐fetoprotein (≥ 8.0 ng/mL; P = 0.030), type IV collagen (≥ 200 ng/mL; P = 0.043), fibrosis‐4 index (≥ 4.14; P = 0.0006), and human leukocyte antigen (HLA)‐DQA1/DRB1 ‐SNP (AA genotype; P = 0.0092) were significantly associated with HCC development according to the log‐rank test. In multivariate analysis, AA genotype in the HLA‐DQA1/DRB1 gene ( P = 0.013; hazard ratio 4.907; 95% confidence interval 1.407–17.113) and cirrhosis ( P = 0.019; hazard ratio 4.789; 95% confidence interval 1.296–17.689) were significantly associated with HCC development. Conclusions: Our findings suggested that patients with AA genotype in the HLA‐DQA1/DRB1 gene or cirrhosis should be carefully followed up as a population potentially at higher risk of HCC during ETV treatment.